O desafio da eficiência do estado democrático de direito no cenário da globalização econômica - Ferreira, Antonio Carlos Gomes (2016)
This dissertation aims to reflect on the challenge of democratic rule of law in the efficiency scenario of economic globalization. Questions the paradigm and institutional crisis of the state focused on its cooptation by hegemonic groups that exert regulatory pressure. This movement ends with reflections in the advancement of social justice, and the principle of efficiency in the post-modern context, related, therefore, aspects of social exclusion. In addition to the theoretical frameworks that reflect post-modernity, there is the comparison of state functions in relation to its structure in modernity as well as a critical reflection on its role from the standpoint of domination. It is expected, therefore, to reflect on the changing role of the state, which, of capitalism support instrument in its genesis, passed the important resistance instance to deregulation forces that cause fragmentation and social exclusion in contemporary times. The approach relates the state with the paradigm of efficiency and social justice seen as one of the corporate goals by the Democratic and Social State of Law.